Depicting Soybean Diversity via Complementary Application of Three Marker Types - Vesna Perić; Natalija Kravić; Marijenka Tabaković; Snežana Mladenović Drinić; Valentina Nikolić; Marijana Simić; Ana Nikolić (Plants)
Driven by the growing demands for plant-based protein in Europe and attempts of soybean breeding programs to improve the productivity of created varieties, this study aimed to enhance genetic resource utilization efficiency by providing information relevant to well-focused breeding targets. A set of 90 accessions was subjected to a comprehensive assessment of genetic diversity in a soybean working collection using three marker types: morphological descriptors, agronomic traits, and SSRs. Genotype grouping patterns varied among the markers, displaying the best congruence with pedigree data and maturity for SSRs and agronomic traits, respectively. The clear origin-related grouping pattern was not observed for any of the marker types. For the diversity assessed by morphological descriptors, Homogeneity Analysis by Means of Alternating Least Squares (HOMALS) yielded the most efficient classification by identifying the traits with the highest discriminative power and separating the genotypes into homogeneous groups. According to genetic distances (GDs), the highest diversity was found for morphological descriptors (GD = 517), followed by SSRs (GD = 0.317) and agronomic traits (GD = 0.244). The analysis of molecular variance (AMOVA) revealed a weak differentiation between geographic groups (ΦST = 0.061), emphasizing the highest differentiation for Canadian genotypes (ΦST = 0.148 **). A low correlation was found between molecular and morphological, i.e., agronomic trait-based matrices (0.061 *, i.e., –0.027, respectively). The overall assessed diversity highlighted the importance of introducing new sources of variation to promote long-term improvement in soybean breeding.